The Experience of Political Office as a Reason for Proficiency - Khalid Khalid (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
President or Vice President and under the age of 40, they must have experience in serving as an elected official through elections, such as members of the DPR, DPD members, DPRD members, Governors, Regents, or Mayors. However, this rule does not apply to directly appointed officials, such as acting or acting officials. Candidates who fall under the category of appointed officials can run for President or Vice President after reaching the age of 40. The existing secondary data collected was also analyzed using the inductive method. Subtilitas intellegendi or the accuracy of understanding and accuracy of explanation of the problem (subtilitas explicandi) of the problem is very relevant to resolving legal issues in this study. In running for a regional head position, it is important to demonstrate maturity and integrity. Focus on experience, a deep understanding of local issues, and concrete plans to move the region forward. Avoid provocative rhetoric and ensure your communications reflect professionalism and responsibility. Capacity to act and authority to act both relate to the event of taking legal action. Legal action is an everyday event, in social life establishing relationships with other members of society. Because legal actions are everyday actions carried out by humans, it is necessary to regulate the capacity and authority to act.